Effects Of Slope Segments On Physical, Hydraulic, and Structural Stability Properties at Three Soil Depths in Amachalla, Awka, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study examines the effects of slope segments in gully site at three depths on soil physical, hydraulic and structural stability properties at Amachalla, Awka, Southeastern Nigeria. A total of 36 soil samples were collected from three different slope segments (upper, middle and lower) at three depths (0–15 cm, 15–30 cm, and 30–45 cm) with four replications.  These samples were prepared and taken to the laboratory for analysis using standard procedures to determine some soil parameters. The laboratory data were analyzed using Genstat Statistical Package and means were separated by Fisher’s Least Significant Difference (F-LSD) at P